Platelet-to-lymphocyte ratio, PELOD-2 score, and mortality rate in pediatric sepsis - Novie Homenta Rampengan; Gregory Joey; Ferry Kurniawan; Jeanette I. Ch. Manoppo; Ari Lukas Runtunuwu (Paediatrica Indonesiana, 2021)
Background Sepsis is life-threatening organ dysfunction caused by a regulated immune response to infection. Sepsis remains the most common cause of death in infants and children worldwide. The Pediatric Logistic Organ Dysfunction (PELOD-2) score, one of the most widely used scoring systems in pediatric sepsis patients, has been shown to be accurate in predicting mortality. The platelet-to-lymphocyte ratio (PLR) is a new clinical indicator of inflammation in a variety of diseases including sepsis. Objective To investigate the relationship between PLR, PELOD-2 score, and clinical outcomes in pediatric patients with sepsis. Methods This retrospective cohort study was conducted in the Pediatric Intensive Care Unit (PICU), Prof R.D. Kandou Hospital, Manado, North Sulawesi, from February to August 2020. Subjects’ PELOD-2 score and PLR were recorded once within the first 24 hours of PICU admission. We analyzed patients’ PELOD-2 score, PLR, and mortality rate, with 95% confidence interval (CI) for each value. Results Of 96 children with sepsis admitted to the PICU during the study period, 87 patients (46 boys; 52.9%) met the inclusion criteria. In total, 50 (57.47%) patients were non-survivors. Mean PLR values among survivors [77.54 (SD 50.08)] was significantly lower compared to the values among non-survivors [157.13 (SD 67.38)]; as well as the PELOD-2 score in the survivors group [12 (SD 1.32)] was significantly lower than its value in the non-survivors [14.65 (SD 2.09)]. Spearman’s analysis showed a moderately positive correlation between PLR and PELOD-2 score (r=0.444; 95%CI 0.44 to 1; P<0.01). Biserial point correlation analysis revealed a significant association between PLR and mortality rate (rpb=0.566; P<0.0001),with elevated PLR related to an increased risk of mortality. Conclusion There are positive correlations between PLR, PELOD-2 score, and mortality rate in pediatric patients with sepsis. Higher PLR and PELOD-2 score are associated with higher mortality.